Colombian ADRs : why so few? (2009)
We address the question of why Colombian companies have had such a limited presence in the ADRs market. Traditional explanations state that investors' protection and the degree of Colombian economic and financial development increases the costs of entry in the ADRs market. However, in the case of Colombia these explanations do not suffice because in these respects Colombia is no different from other Latin American countries. Using a theoretical model, we show that additional factors such as drug trafficking and armed conflict explain better why Colombian firms have moved away from the ADRs market.